(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
While analyzing a song we can concentrate on its three main aspects: how we look at the song, how we respond to the song and how we think about the story in the lyrics. A song is lyrics and music that illuminate a particular reality. We focus on places and people it mentions, on the sounds we hear, on the personal reactions to the lyrics, the music and the imagery it evokes. We often think about the artist and why he/she wrote a particular song and what it tells us about life in general. It refers to what David Fillingim says, that “music should not only entertain; it should make the world a better place” (2003: 93). Country music typically represents the epic – lyric opposition which is emphasized in cyclical songs and the “timelessness of (its) themes.” (Fox, 2004: 236–237). The timeless themes analyzed in this chapter were Southern patriotism, politics and religion. The imaginary moments of utopia, shared values and ideals, bring people together and keep them together, as well as the culture they grew up in does. Music creates community relationships, it works as a process of social bonding “for integration of individual selves, for imagining the possible, for explaining the actual and for flow.”(Turino, 2008: 181, 227). Through the lyrics of their songs, country musicians show how they perceive the world around them “to invoke an ironic, nostalgic, patriotic, sacred, polemical, frightening, and unstable image” (Fox, 2004: 76). They interpret and comment on the political reality they live in and share their opinions and personal experience with the listeners. Religion, as a cultural institution, is a sphere of musical practice. Musical techniques specific to country are used to pass the spiritual message to the recipients. Country fans like it because the songs explain complicated issues in simple words. Using colloquialisms, they stress out ordinary emotions and use simple narratives to tell stories their listeners can refer to. Country music is part of the Southern identity because of its bonding power. Songs about politics and Southern patriotism invite one to participate in the national discussion where everyone has the same right to comment on the issues. Country artists speak about difficult matters in a simple language. That is why their voice is so recognizable. The following paper synthesizes my research of the influence of the “voice” of country music in the construction of the Southern Identity through the ideals of the Imaginary South.